Study on the effect of mindfulness Taijiquan on improving mobile phone addiction behavior and inhibiting function of college students - Li, Jizhao; Yang, Wanjiao; Zheng, Fang (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Research purpose: mobile phone addiction (MPA) refers to an addictive behavior in which excessive use of mobile phones under the premise of non-substance addiction causes adverse physiological and psychological consequences to individuals, which is manifested by strong craving for mobile phones, loss of control, psychological dependence and impaired life function. The high prevalence rate of MPA in Chinese college students is 21.3%.At present, the intervention research of MPA is still in the stage of theoretical development, mainly focusing on cognitive therapy and exercise therapy. As a positive personality trait, mindfulness can influence college students’ mobile phone addiction. The reason may be that individuals with a high level of mindfulness have a higher level of attention, are more likely to pay attention to current activities, reduce individual redundancy and increase the control of negative thinking, and ultimately improve the overall cognitive ability. Mindfulness Tai Chi intervention is helpful to improve addictive behaviors such as Internet addiction and drug addiction and improve executive function. There is growing evidence that both acute and long-term mindful tai chi interventions can improve executive function and cognitive ability in different populations. Executive function is more closely related to phone addiction. Of these, inhibitory function, which enables an individual to focus on task-relevant information and suppress irrelevant information, is most directly associated with a person’s addictive or health behavior, but the relationship between these variables remains unclear.The purpose of this study was to explore the effects of 8-week mindful Tai Chi intervention on mobile phone addiction, level of mindfulness, executive function and various sub-functions of college students, and to explore the possible mechanism of improving mobile phone addiction in college students through mindful Tai Chi intervention.Research methods: In this study, students from a university in Beijing were selected as the research subjects, and those with scores higher than 40 points were selected by using the mobile phone Addiction Index (MPAI) scale. Cardiovascular diseases, respiratory diseases, bone and joint diseases, depression and anxiety disorders were excluded. Finally, 66 subjects with an average age of 18 to 21 were included in the study. They were randomly divided into control group (33 people) and experimental group (33 people).The control group maintained the normal level of physical activity without additional intervention, while the experimental group received 8 weeks of mindfulness tai Chi intervention. The Tai Chi part of the intervention used was based on Yang’s Tai Chi movements, while the mindfulness part included mindfulness no-extremity post and soothing and soft music to guide the practitioners to focus on themselves and return to inner peace. The exercise time was 40min each time. Among them, the non-pole pile exercise with mindfulness guidance language was 5min, the eight-style Tai Chi exercise was 30min (4min*6 sets, 1min interval between groups), and the relaxation part of the non-pole pile with music was 5min, and the exercise frequency was 3 times a week.The mobile phone addiction Scale (MPAI) developed by Liang Yongchi was used to evaluate the situation of mobile phone addiction before and after the intervention, and the mindfulness Attention Awareness Scale (MAAS) prepared by Brown and Ryan in 2003 was used to evaluate the level of mindfulness before and after the intervention. The executive function test tool was used to evaluate the executive function, including Flanker task (suppression function), 2-back task (refresh function) and More-odd shifting task (transformation function). The test indexes were reaction time (milliseconds) and correct rate (%). 2 (time: pre-test and post-test) ×2 (group: experimental group and control group) was used for repeated measurement ANOVA, Pearson was used for correlation analysis between variable quantities, and Model4, a new mediation effect program proposed by Wen Zhonglin et al., was used for mediation effect test.The results were as follows: (1) Cell phone addiction (t = -0.110, P = 0.913 > 0.05), mindfulness level (t = 0.883, P = 0.381 > 0.05) and subfunctional inhibition of executive function (correct rate t = -0.861, P = 0.393 > 0.05; Reaction time t = -0.876, P = 0.384 > 0.05), refresh function (correct rate t = -0.448, P = 0.656 > 0.05; Reaction time t = -0.046, P = 0.963 > 0.05) and conversion function (correct rate t = 1.165, P = 0.248 > 0.05; There was no significant difference in t = 0.046, P = 0.963 > 0.05), which showed homogeneity.(2) There was a significant difference in mobile phone addiction index between the experimental group and the control group after 8-week mindfulness tai Chi intervention (F = 6.167, P = 0.016 < 0.05), and there was a significant difference in mindfulness level between the experimental group and the control group after 8-week mindfulness Tai Chi intervention (F = 4.146, P = 0.046 < 0.05) and the sub-functional levels of executive function in the post-test experimental group and the control group, including the accuracy rate of inhibitory function (F = 15.466, P = 0.000 < 0.01), the accuracy rate of inhibitory function response (F = 13.330, P = 0.001 < 0.01), and the accuracy rate of refreshing function (F = 0.405, P = 0.527 > 0.05), refresh function response (F = 1.078, P = 0.303 > 0.01) and conversion function accuracy (F = 12.474, P = 0.001 < 0.01);(3) Before and after mindfulness Tai Chi intervention, the decrease of mobile phone addiction index was correlated with the change value of inhibitory function response (r = 0.756, P=0.000 < 0.01), the change value of refreshing function response (r = 0.035, P=0.045 < 0.05) and the change value of switching function response (r = 0.397, P=0.045 < 0.05). P=0.022 < 0.05) pairwise correlation was significant; There was significant correlation between the increase of mindfulness level and the change value of inhibitory functional response (r = 0.394, P=0.023 < 0.05).(4) The improvement of mindfulness level had a significant predictive effect on the decline of mobile phone addiction index (B = 1.199, t =4.1892, p=0.0002<0.01), and the direct predictive effect of the improvement of mindfulness level on the decline of mobile phone addiction index was still significant after adding the intermediary variables (B = 0.716, t =3.1968, p=0.033<0.05). The improvement of mindfulness level was significant in predicting the change of inhibitory function (B=0.283, t = 2.388, p=0.023<0.05), and the improvement of inhibitory function was also significant in predicting the decline of mobile phone addiction index (B= 1.7081, t = 5.575, p= 0.000<0.01). The change of inhibitory function in executive function played a partial mediating role in the influence of the improvement of mindfulness level on the decline of mobile phone addiction, and its direct effect (0.716) and intermediary effect (0.483) accounted for 59.72% and 40.28% of the total effect (1.199), respectively.Conclusion: 8-week mindful Taijiquan intervention can improve the mobile phone addiction and the level of mindfulness, as well as the inhibition function, refresh function and conversion function in the executive function. The change of mobile phone addiction index was positively correlated with the change of inhibitory function, refresh function and conversion function, while the change of mindfulness level was only correlated with the change of inhibitory function. The improvement of mindfulness level can not only directly predict the decrease of mobile phone addiction index, but also predict the decrease of mobile phone addiction index through the mediating effect of inhibition function change. The improvement of inhibition function may be the mediating effect of the improvement of mindfulness level before and after the 8-week mindfulness Tai Chi intervention. This study provides theoretical and practical basis for mobile phone addicted college students to adopt reasonable exercise means.